Motivasi Belajar Ditinjau dari Iklim Kelas pada Siswa/Siswi Jurusan IPS - Cindy Wiliem; Sri Hartini; Diny Atrizka (Fakultas Psikologi, Universitas Putra Indonesia YPTK Padang, 2020)
The purpose of this research is to determine the relationship between classroom climate and learning motivation. The hypothesis submitted in this research is, there is a positive relationship between classroom climate and learning motivation, with assumption the more conducive classroom climate perceived by students, the higher learning motivation of students and vice versa. The research subjects used in this study were high school students in Methodist 2 with a major of Social Sciences as many as 182 people selected by the disproportionate stratified random sampling method. The method of analysis data used for this research is Product Moment correlation through SPSS 17 for Windows. The results of data analysis showed r = 0.575 and p = 0.000 (p <0.05) which means that there is a positive relationship between classroom climate and learning motivation. The results of this research show that the contribution (R2) given the classroom climate variable to learning motivation was 33.1 percent, the rest 66.9 percent was influenced by other factors not examined in this research. From the results of this research it can be concluded that the research hypothesis there is a positive relationship between classroom climate with learning motivation, can be accepted.